An Overview of Recent Patents on Nanosuspension - Modh, Nirav; Mehta, Dharmik; Parejiya, Punit; Popat, Amirali; Barot, Bhavesh (Recent Patents on Drug Delivery & Formulation, 2014)
Pharmaceutical scientists involved in drug discovery and drug development are facing serious problems with newer poorly water soluble drugs with respect to their dissolution and bioavailability. Reducing the particle size of active pharmaceutical ingredient has been an efficient and reliable method for improving the bioavailability of insoluble drugs. Nanosuspension has emerged as an efficient and promising strategy for delivery of insoluble drugs due to its unique advantages such as ease of modification, process flexibility, targeting capabilities, altered pharmacokinetic profile leading to safety and efficacy. These unique features of nanosuspension have enabled its use in various dosage forms, including specialized delivery systems such as oral, parenteral, peroral, ocular and pulmonary routes. Currently, efforts are being directed to extend their applications in site-specific drug delivery. Large numbers of products based on nanosuspension are in the market and few are under clinical trials. The commercialization potential of nanosuspension based formulation for oral route is well established and products for other routes will enter the market within short span. Among the various techniques available, only wet milling technique has been successfully used for commercial production of nanosuspension. Nanosuspension based patents have extensive potential of reaching faster in the market as compared to other nanotechnology based formulations. This review covers various aspects of techniques of preparation, route of administration and commercialization of nanosuspension with main focus on the recent patents granted in the field.
Keywords: patents